BLOCKCHAIN AND SMART PORTS IN THE BLACK SEA BLUE ECONOMY - Yarovyi, Viktor (SWorld-Ger Conference proceedings, 2025)
The Black Sea region has experienced significant transformation in maritime logistics, driven by the adoption of digital technologies such as blockchain, artificial intelligence (AI), and the Internet of Things (IoT). This paper examines the current state